PERLINDUNGAN HUKUM TERHADAP PARA PIHAKDALAM PERJANJIAN HUTANG PIUTANG PADA PERUSAHAAN TEKNOLOGI FINANSIAL - Najla Putri Salma, - (2019)
The development of banking services with the inception of the financial technology increasingly facilitates the community in meeting its needs. One of the financial technology products is in the area of debt - or accounts receivable based on information technology. These services are community-wide interest because it is more efficient than the conventional banks that process without going through direct face-to-face. Covenant debt receivables-based technology often occurred violations by either party to the debtor nor the creditor so that the tort occurred to the detriment of the parties. This study uses empirical juridical approach, the data sources used are primary data, obtained from the results of the interviews one of the applicant's loan-based financial technology failed to pay and did not get the protection of the law as the debtor. Based on studies of the debtor is entitled to judicial protection has been provided for in law No. 8 Year 1999 on the protection of consumers and Regulation OJK number 1 Year 2013 on the protection of consumers of financial services sectors. Dispute resolution in the agreement debt receivables-based finansianl technology is the non litigation i.e. through negotiation